Aplicação de transdutores óticos para a monitoração da qualidade de biocombustíveis - Kawano, Marianne Sumie (2015)
In the present work were studied the responses of the optical sensors based on cascaded long period gratings (CLPG) to evaluate biofuels (soy biodiesel and ethanol) in different situations of non-compliance, simulating cases of possible tampering or failures in the process of manufacturing. To this end, the devices served as refractive index transducers of the analyzed substances. One of the applications of the sensors were evaluate mixtures of soybean biodiesel and commercial soybean oil, observing the performance of the optical sensor over the whole range of biodiesel oil concentration (0 - 100%) and the metrological characteristics were calculated for three system operating ranges covering different concentration ranges. In lanes 1 through 3, the sensitivity ranged from 0.06 to 0.30 nm /% v / v and the resolution from 0.17 to 0.03% / v / v. In order to compare the results, the same samples of biodiesel oil, were assessed by ultrasound techniques for obtaining this, a sensitivity of 0.70 m / sec / v / v% and resolution of 0.4%. Another situation studied envolved mixtures of soybean biodiesel and methanol and the response of the optical sensor showed resolution from 0.007 to 0.001% / v / v. Through these responses could be developed an analytical method which uses the optical sensor for the determination of constituents of ternary mixtures (biodiesel - soybean oil - methanol) associating to the sensor the right temperature of the samples. Another part of the work, the optical sensor was used in the evaluation of ethanol. The sensor response for ethanol-methanol mixtures showed resolution of 0.19% / v / v, while the evaluation of those substances using ultrasound, showed resolution of 0.26% / v / v. Another situation observed using the optical sensor was the analysis of ethanol fuel with samples having ternary mixtures (ethanol-methanol-water) in which the evaluation of these mixtures by means of a refractometer Abbe and density measurements made necessary. The results presented in these analyses are promising when related the refractometric to densities datas obtained for each sample, since only one of these parameters would not be able to identify the product conformity. It was then possible to determine, among all results, a compliance region for ethanol fuel.